2015
DOI: 10.1080/10548408.2015.1008666
|View full text |Cite
|
Sign up to set email alerts
|

Critical In-Flight and Ground-Service Factors Influencing Brand Prestige and Relationships Between Brand Prestige, Well-Being Perceptions, and Brand Loyalty: First-Class Passengers

Abstract: This study (1) proposes optimal in-flight and ground services for maximizing the brand prestige of passengers taking first-class flights; (2) investigates the relationships between brand prestige, passengers' well-being perception, and brand loyalty; and (3) tests the moderating effect of status consumption. To empirically test the proposed conceptual model, a survey was conducted using a sample of passengers who experienced first-class flights with any airline by an online market research firm in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 74 publications
2
27
0
1
Order By: Relevance
“…It would also be interesting to conduct LSA analysis to different online customer generated reviews such as Skytrax, Twitter and Facebook, as well as comparing the results of different websites. Ahn et al, 2015;Kim et al, 2016 Service Performance Ahn et al, 2015;Kim et al, 2016 Flight crew (courtesy, helpfulness and friendly)   (7) Vlachos and Lin, 2014; Chen and Chao, 2015; Kim and Park, 2017 Professionalism of staff Forgas et al, 2010 Assurance (Courtesy and knowledge) Leong et al, 2015;Calisir et al, 2016;Rajaguru, 2016 Cabin/Aircraft Seat comfort   (6) Medina- Muñoz et al, 2018;Forgas et al, 2010;Han et al, 2014;Chen and Chao, 2015;Kim and Park, 2017 Cabin (Interior)  (7) Vlachos and Lin, 2014;Han et al, 2014;Chen and Chao, 2015 In-flight baggage space Medina-Muñoz et al, 2018;Kim and Park, 2017 Odour, temperature, air quality, noise Han et al, 2014 Airline Tangibles Suki, 2014;Kim et al, 2016;Kos Koklic et al, 2017;Leong et al, 2015;Calisir et al, 2016;Rajaguru, 2016 Aircraft type Chen andChao, 2015 Environment and facilities In-Flight entertainment Ahn et al, 2015  (11) Ahn et al, 2015Medina-Muñoz et al, 2018;Kim et al, 2016;Han et al, 2014;Chen and -Muñoz et al, 2018;Forgas et al, 2010;Vlachos and Lin, 2014;…”
Section: Limitations and Future Research Suggestionsmentioning
confidence: 99%
“…It would also be interesting to conduct LSA analysis to different online customer generated reviews such as Skytrax, Twitter and Facebook, as well as comparing the results of different websites. Ahn et al, 2015;Kim et al, 2016 Service Performance Ahn et al, 2015;Kim et al, 2016 Flight crew (courtesy, helpfulness and friendly)   (7) Vlachos and Lin, 2014; Chen and Chao, 2015; Kim and Park, 2017 Professionalism of staff Forgas et al, 2010 Assurance (Courtesy and knowledge) Leong et al, 2015;Calisir et al, 2016;Rajaguru, 2016 Cabin/Aircraft Seat comfort   (6) Medina- Muñoz et al, 2018;Forgas et al, 2010;Han et al, 2014;Chen and Chao, 2015;Kim and Park, 2017 Cabin (Interior)  (7) Vlachos and Lin, 2014;Han et al, 2014;Chen and Chao, 2015 In-flight baggage space Medina-Muñoz et al, 2018;Kim and Park, 2017 Odour, temperature, air quality, noise Han et al, 2014 Airline Tangibles Suki, 2014;Kim et al, 2016;Kos Koklic et al, 2017;Leong et al, 2015;Calisir et al, 2016;Rajaguru, 2016 Aircraft type Chen andChao, 2015 Environment and facilities In-Flight entertainment Ahn et al, 2015  (11) Ahn et al, 2015Medina-Muñoz et al, 2018;Kim et al, 2016;Han et al, 2014;Chen and -Muñoz et al, 2018;Forgas et al, 2010;Vlachos and Lin, 2014;…”
Section: Limitations and Future Research Suggestionsmentioning
confidence: 99%
“…They showed that when passengers feel that their QOL is enhanced, they would take the cruise in the future. Ahn et al [17] proposed a theoretical model in order to find the relationship between WBP and BI using 205 first-class passengers. They suggested that when customers have a high level of WBP, they are willing to take first-class flights in the future.…”
Section: Wellbeing Perception (Wbp)mentioning
confidence: 99%
“…As brand prestige has received much attention in the hospitality and tourism industry including luxury cruise, first-class flights, private country clubs, and casinos, it has been studied by many scholars [3,17,19,20]. The concept of brand prestige is defined as a relatively higher status of products/services positioning related to a brand when compared with other competing brands [21,22].…”
Section: Brand Prestigementioning
confidence: 99%
“…Consumers are willing to accept the high price of prestige brands for their benefits and associated values (Debnam and Svinos, 2007; Rauscher, 1992). The relatively high status of certain brands, which is regarded as ‘brand prestige’ (BP) in the literature, enhances customer satisfaction, stimulates purchase intention, and develops brand trust, attractiveness, identification, and loyalty (Ahn et al, 2015; Baek et al, 2010; Choi et al, 2011; Currás-Pérez et al, 2009; Hwang and Han, 2014; Hwang and Hyun, 2012; Jin et al, 2015; Ok et al, 2011). Therefore, managers spend millions of dollars to enhance the BP of their companies (Naik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%